2013
DOI: 10.1128/mcb.00813-13
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Autophagy by the Methyltransferase G9a

Abstract: Macroautophagy is an evolutionarily conserved cellular process involved in the clearance of proteins and organelles. Although the cytoplasmic machinery that orchestrates autophagy induction during starvation, hypoxia, or receptor stimulation has been widely studied, the key epigenetic events that initiate and maintain the autophagy process remain unknown. Here we show that the methyltransferase G9a coordinates the transcriptional activation of key regulators of autophagosome formation by remodeling the chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 44 publications
9
163
1
Order By: Relevance
“…Moreover, all WIPI genes were found to be aberrantly expressed in different human tumors (Box 1) (Proikas-Cezanne et al, 2004). WIPI1 gene expression is positively regulated by TFEB in liver (Settembre et al, 2013) and by PU.1 during neutrophil differentiation , and is epigenetically repressed by the histone methyltransferase G9a (also known as EHMT2) (Artal-Martinez de Narvajas et al, 2013). Interestingly, upon starvation or activation of naive T cells, G9a dissociates from the WIPI1 promoter, leading to increased WIPI1 expression upon induction of autophagy (Artal-Martinez de Narvajas et al, 2013).…”
Section: The Human Wipi Gene and Protein Familymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, all WIPI genes were found to be aberrantly expressed in different human tumors (Box 1) (Proikas-Cezanne et al, 2004). WIPI1 gene expression is positively regulated by TFEB in liver (Settembre et al, 2013) and by PU.1 during neutrophil differentiation , and is epigenetically repressed by the histone methyltransferase G9a (also known as EHMT2) (Artal-Martinez de Narvajas et al, 2013). Interestingly, upon starvation or activation of naive T cells, G9a dissociates from the WIPI1 promoter, leading to increased WIPI1 expression upon induction of autophagy (Artal-Martinez de Narvajas et al, 2013).…”
Section: The Human Wipi Gene and Protein Familymentioning
confidence: 99%
“…WIPI1 gene expression is positively regulated by TFEB in liver (Settembre et al, 2013) and by PU.1 during neutrophil differentiation , and is epigenetically repressed by the histone methyltransferase G9a (also known as EHMT2) (Artal-Martinez de Narvajas et al, 2013). Interestingly, upon starvation or activation of naive T cells, G9a dissociates from the WIPI1 promoter, leading to increased WIPI1 expression upon induction of autophagy (Artal-Martinez de Narvajas et al, 2013). WIPI2 gene expression has been found to be negatively regulated by ZKSCAN3, a master transcriptional repressor of autophagy and lysosome biogenesis (Chauhan et al, 2013).…”
Section: The Human Wipi Gene and Protein Familymentioning
confidence: 99%
“…This mechanism is also found in mammals [4551]. Thus, MAPK8/9 may promote autophagy by increasing the expression of ATG4 (autophagy related 4) [49], ATG5 [45], BECN1 [48], BNIP3 (BCL2/adenovirus E1B interacting protein 3) [47,50], LC3B [46,51], and SQSTM1 [46]. MAPK8/9-regulated gene expression therefore represents an evolutionarily conserved mechanism of autophagic regulation.…”
Section: Discussionmentioning
confidence: 99%
“…His group demonstrated that depletion of the histone methyltransferase G9a by short hairpin (sh) RNA or using chemical inhibitors of G9a in pancreatic cancer cells resulted in increased expression of genes promoting the cell cycle (e.g., p21/Cdkn1a and p27/Cdkn1b ), enlargement of lysosomes, and increased levels of LC3B-II, a protein marker of autophagy. They further found that G9a is normally associated with the promoters of autophagy related genes LC3B, WIPI1 , and DOR , where G9a mediates repression of these genes [21]. Upon induction of autophagy by glucose starvation, G9a, H3K9me3, and H3K9me2 were decreased at these promoters, contributing to increased expression of LC3B, WIPI1 and DOR.…”
Section: Epigenetic Mechanisms In Neoplastic Diseasesmentioning
confidence: 99%